ANALISIS FAKTOR KESULITAN GURU BIDANG STUDI EKONOMI DALAM PELAKSANAAN PEMBELAJARAN KURIKULUM 2013 - Juni Karsela Indrawati; Achmadi Achmadi; Okianna Okianna (Universitas Tanjungpura, 2019)
Abstract Learning researcher for teacher learnig in Economic in learning implementation 2013 curriculum at SMAN 2 Pontianak. This type of research was a type of qualitative research. The research subject was the teacher in the field of economic studies. The data analysis technique in this study used was descriptive analysis. In this study, data collected from interviews and direct observation. The results showed that the teacher corrected several factors in the implementation of the 2013 learning at SMAN 2 Pontianak. The implemented of the 2013 curriculum has been implemented, but there were several difficulty factors faced in the process of implemented the 2013 curriculum. From the results obtained through interviews with economic teachers who concluded: 1) from the results of interviews and observations made by researchers at SMAN 2 Pontiana, can be simplified the learning process of the 2013 curriculum running well. 2) in the implementation of the 2013 curriculum, the teacher corrected a number of difficulties, the socialization provided by the government inthe 2013 curriculum changes and the lack of existing facilities and infrastructure were processed. Approved facilities and infrastructure, namely, prefer projector 9infocus), lower textbooks, and lower approved fans. The makes the implementation of the 2013 curriculum at SMAN 2 Pontianak less affective with maximization. 3) Efforts made bye teachers are to use existing facilities and infrastructure as possible. In addition, the teacher also gave advice to the principal to make a budget for improving facilities and insfrastructure in the school of SMAN 2 Pontianak. Keywords:Curriculum 2013, Factors Difficulties Teachers, Implementation of Learning